Synthesis, characterization, and application of calcium methoxide as heterogeneous catalyst for trimethylolpropane ester conversion reaction - Masood, Hassan (2011)
Trimethylolpropane esters (TMPE) hold the potential as biolubricant basestock. This research was conducted with an aim to study the synthesis, characterization and application of calcium methoxide as heterogeneous catalyst for production of TMPE. Calcium methoxide was synthesized utilizing a two stage process through calcination and reflux. The synthesis process was optimized by studying the effect of various factors, and the optimum conditions were found to be: calcination time 1.5 hr, amount of methanol 100 mL, and reaction time 2 hr. Synthesized and commercial calcium methoxide were characterized by X-ray diffraction (XRD), fourier transform infra-red spectroscopy (FTIR), Brunauer-Emmett-Teller (BET) surface area measurement, particle size distribution, scanning electron microscopy (SEM),energy-dispersive X-ray spectroscopy (EDX) and thermogravimetric/simultaneous differential thermal analysis (TGA/SDTA). The XRD results revealed calcium methoxide was successfully synthesized with good purity. The comparison of XRD diffractogram of synthesized and commercial calcium methoxide showed acceptable results. FTIR and EDX results further confirmed the similarities between synthesized and commercial calcium methoxide in terms of having same functional groups and nearly same quantitative composition of calcium, oxygen and carbon. SEM results displayed thermally resistant surface structure with good porosity; BET showed high surface area; particle size analysis evidenced reasonable particle size; and TGA/SDTA revealed good thermal stability of synthesized calcium methoxide. Moreover, it was found to possess mesoporous surface by Barrett–Joyner–Halenda (BJH) method. The results of transesterification reaction proved good catalytic activity of both synthesized and commercial calcium methoxide, and more than 90% yield of trimethylolpropane triesters was obtained after 8 hr reaction time. Overall, this research successfully reported the synthesis of calcium methoxide and its effectiveness to act as a heterogeneous catalyst for conversion of trimethylolpropane (TMP) and palm oil methyl esters (POME) to TMPE.